Current advances in treatment of gastroparesis. (September 2015) - Malamood, Mark; Parkman, Henry; Schey, Ron
Abstract : Introduction: Gastroparesis is a syndrome defined by delayed gastric emptying in the absence of mechanical obstruction. Gastroparesis has significant symptomatology and negative impacts on the patient's quality of life. Areas covered: This article reviews current treatment options for gastroparesis, recent advances in treatment and future directions that treatment may head. Current options are broadly divided into prokinetics and symptom modulators. Within each group, current modalities as well as recent advances are discussed according to agent mechanism of action. Lastly, findings regarding the cellular pathophysiology involved in gastroparesis will be briefly reviewed along with their implications for future treatments. Expert opinion: The numerous motor functions and neural inputs that control gastric motility are complex and not fully understood. Our lack of understanding of its pathophysiology has led to treatment options which are empirical, palliative and often ineffective. Newly intensified interest in the cellular pathophysiology behind gastroparesis provides promise for a new era of treatments. Identification of common cellular changes in gastroparesis has provided targets for treatment that may allow us to one day better treat the symptoms of gastroparesis related to its underlying pathophysiology. This is the future of gastroparesis therapy.